Improving Literacy in Early Childhood (4-5 Years) Through Morning Journal Activities at Pembina Aba 54 Kindergarten in Semarang - Hilda Purbaranie; Mustakimah Mustakimah (Journal of Educational Sciences, 2026)
The golden age is an ideal period for developing various skills, including language literacy. Children need various literacy skills to understand many subjects and achieve the objectives of each subject, improving their understanding of knowledge, skills, and attitudes. Literacy does not only refer to the ability to read and write. The latest definition of literacy refers to the skills of understanding, receiving, using, analyzing, and transforming information. One way to improve literacy skills in early childhood is through morning journaling activities. This study aims to determine whether morning journaling activities can affect literacy skills in early childhood. The study was conducted using a qualitative descriptive method. Data collection was carried out through observation, interviews, and documentation. The results showed that literacy habits through morning journaling activities can contribute to improving children's literacy skills. Thus, language skills will also improve and align with the developmental stage the child has reached. Reading literacy through morning journals allows children to practice expressing themselves in their own language according to the journals created by early childhood. Through morning journaling activities, children can develop literacy skills that influence their reading, writing, and communication.